Influence of proprioceptive training based on ankle-foot robot on improving lower limbs function in patients after a stroke - Mao, Yajun; Gao, Zhenzhen; Yang, Hang; Song, Caiping (Frontiers in Neurorobotics, 2022)
Background: Proprioception is important for our everyday activity, as it indicates the position, movement and force to the body. This is important not only for the ambulation, but also for patients who are diagnosed with stroke. Objective: To evaluate the influence of the proprioceptive training based on the ankle-foot robot to the lower limbs function in patients after stroke. Method: Sixty adult participants who met the criteria were randomly divided into a control group and an experimental group. The control group (RG) was given regular physical activity, and the sensory training group (SG) was given proprioceptive training based on an ankle-foot robot, the rest being the same as RG. Measurements for 10-Meter Walking Time (10MWT), Berg Balance Scale (BBS), Fugl-Meyer assessment lower extremity (FMA-LE), and active range of motion (AROM), passive range of motion (PROM), ankle joint sensitivity before and after six weeks of treatment (30 sessions; five times per week). Results: There were a significant decrease in both 10MWT and ankle joint sensitivity in both groups (p＜0.05), while there were statistical increase of BBS, FMA-LE, AROM, PROM in both groups (p＜0.05). A significant relationship was identified between the two groups, the SG group had greater degrees of improvement compared with the RG group. Conclusion: The proprioceptive training based on an ankle-foot robot could improve proprioception, and effectively improve the motor function and walking ability in patients after stroke. Proprioceptive strength training is recommended to be emphasised on the regular rehabilitation in patients after a stroke.